Konsep Reward and Punishment dalam Al-Qur’an (Kajian dari sisi Penerapan Pendidikan Moral) - Junaidi Junaidi (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2019)
The learning process will run well if it is supported by several things, including student discipline in school as the order, ethics, and norms that must be upheld to succeed the learning objectives. Educators must apply wisdom in choosing and using the most appropriate method. Among them there is enough by example and advice, so there is no need for punishment for him. But psychologically the students were not all the same, some of them also needed to be raped or punished, namely those who made mistakes. The assumption that has developed so far in society is that every mistake must be punished; God also punishes everyone who is guilty. From one logical path that theory has a point. It is logical, everyone who is guilty must be punished; every person who does good must be rewarded. Actually punishment does not always have to have a negative connotation which results in misery for the convicted but can also be positive.